Answer: The equation of the perpendicular line intersects the point (-5,1) is y=x+6[/tex]
Step-by-step explanation:
step1:-
The standard form of slope - intercept form y=m x+c
Here m is called slope of the given line
C is called the y- intercept of the given line
Given equation of the straight line y=-x+1
comparing the slope - intercept form y=m x+c
here m= -1 and c=1
step2:-
The equation of the perpendicular line is
[tex]y-{[y_{1}[/tex]} =\frac{-1}{m} (x-x_{1} )[/tex]
substitute m = -1 and c =1 values in equation
[tex]y-1 =\frac{-1}{-1} (x-(-5 )[/tex]
[tex]y-1 ={1} (x-(-5 )[/tex]
[tex]y=1+x+5
\\y=x+6[/tex]
step3:- The equation of the perpendicular line intersects the point (-5,1) is
y=x+6[/tex]
conclusion:-
The equation of the perpendicular line is
y=x+6[/tex]